Research on Node Bandwidth Scheduling Algorithm for Ultraviolet Optical Communication Network Based on Credit Mechanism - Ma, Xiangyao; Wang, Leitao; Wang, Jinkui; Han, Wenzhuo; Cao, Jinglin; Wang, Jingyuan; Li, Jianhua (2024 9th International Conference on Electronic Technology and Information Science (ICETIS), 2024)
UV optical communication and its networking applications are currently limited by performance parameters, such as transmission distance and bandwidth. Under bandwidth-constrained conditions, the study of efficient node scheduling algorithms to solve the effective transmission of multiple services has become one of the critical issues in the research of UV optical communication networks. In traditional scheduling algorithms, network nodes have problems such as slow scheduling speed and congestion when facing massive service flows. And under bandwidth limitations, it is even more challenging to deal with many services effectively. In this paper, for the data transmission problem under bandwidth-constrained conditions in UV networks, a credit-based scheduling algorithm with a bandwidth allocation function is designed, which can provide differentiated service guarantees for different priority services and adjust the bandwidth allocation strategy accordingly with the changes of application scenarios. The method can provide more reasonable and efficient bandwidth allocation for UV networks, improving network performance.